The Cytotoxic Effect of Polygonium cognatum and Chemotherapeutic Effect of Doxorubicin on Glioblastoma Cells - Pehlivan, Melek; Karahan Çöven, Hatice İlayhan; Çerçi, Burcu; Eldem, Aslı; Öz, Tuba; Savlak, Nazlı; Soyöz, Mustafa; Pirim, İbrahim (European Journal of Therapeutics, 2021)
Objective: Glioblastoma multiforme (GBM) is an aggressive malignant brain tumor common in adults. Owing to the present difficulty in treating GBM, developing alternative methods is of utmost importance. Recently, the efficacy of various plant extracts in cancer treatment have been evaluated. Polygonum cognatum (P. cognatum) known as ‘Madımak’ is used in herbal medicine in Turkey. Methods: In this study, we investigated the cytotoxity of P. cognatum in the treatment of glioblastoma and its contribution to the effectiveness of doxorubicin (DXR). In the U87 cell line of the P. cognatum and doxorubicin administered at different doses, IC50 doses were determined using the 2,3-Bis-(2-Methoxy-4-Nitro-5-Sulfophenyl)-2H-Tetrazolium-5-Carboxanilide (XTT) method and the effects of combined administration at these doses were examined (respectively 10–125 µg/ml and 0.1–10 µg/ml at 24, 48, and 72 h). Results: P. cognatum extract decreased the cell viability of U87 cells in a time and concentration-dependent manner. It also increased the apoptotic effectiveness of DXR in U87 cells. Conclusion: This is the first preliminary study that investigates the treatment of P. cognatum on glioblastoma in vitro. Further studies are required to investigate the effect of the extract on healthy human cells and to understand signaling pathways.